THE IMPORTANCE OF CONSULTING IN CONTEMPORARY BUSINESS MANAGEMENT - Vukotić, Svetlana; Aničić, Jugoslav; Vukotić, Radovan (Journal of process management and new technologies, 2017)
Modern business is characterized by risk and uncertainty, and such an environment is reflected in the decisions taken by managers. On the other hand, management consulting is one of the most important management techniques developed over the last fifty years. The secondary effect of this invention is the rapid development of new frameworks, tools, and techniques improving the operations in a number of companies. Exposure of consulting organizations to varying combinations of business circumstances and experiences of different companies have allowed for the accumulation of valuable knowledge and business experience. From this coupling, or interaction of knowledge and experience of consulting companies, on the one hand and the needs of management companies to recognize their role and hire consultants, on the other hand, developed the importance of financial consulting and auditing. Rational management processes cannot be imagined without reliable information provided by the audit, especially as the strategic management includes the control phase. The importance and relationship between consulting and management in companies that do business according to modern principles is a central topic of consideration in this paper.